Topic collections, 1938-1956. (Mass observation online. Update., 1945)
Mass Observation's reports and studies into the Victory celebrations in the United Kingdom at the end of World War II. Consisting of diary extracts, reports, interview responses and other relevant printed material, this collection is a record of reactions to the end of war over the periods leading up to and including VE Day (8 May 1945) and VJ Day (15 August 1945). Included is a review of the planned Victory Day, 8 June 1946, in the form of directive responses, questionnaires and reports.